NEW METHODS OF ASSESSMENT OF SUBCLINICAL CHANGES IN THE CARDIOVASCULAR SYSTEM IN ARTERIAL HYPERTENSION - Zh. D. Kobalava; Yu. V. Kotovskaya; A. V. Bogomaz (Столичная издательская компания, 2016)
The heart is related with vascular system anatomically and functionally. Structural and functional changes in the arterial bed increase afterload on the left ventricle (LV), and can change its function, leading to the restructuring of the LV adaptation. Systolic blood pressure (SBP) in the aorta, directly reflecting the load on the LV, differs significantly from the SBP in the brachial artery due to delaying the occurrence of a reflected wave in the aorta. Left ventricular-arterial interaction is a concept that helps to understand the various options for the «optimal» functioning of the cardiovascular system, the effects of changes in the arterial bed to heart function. Methods of analysis of left ventricular-arterial interaction, clinical consequences of the breach and the effects of antihypertensive therapy are presented in the review; the results of the authors own studies are also presented.